2018
DOI: 10.1089/bfm.2018.0032
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Herbal Compresses for Maternal Breast Engorgement at Postpartum: A Randomized Controlled Trial

Abstract: Among the postpartum mothers who had breast engorgement, the herbal compresses could decrease breast engorgement pain. The pain reduction after herbal compresses was found to be greater than with the hot compresses.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
28
0
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 17 publications
(31 citation statements)
references
References 12 publications
2
28
0
1
Order By: Relevance
“…17 The hot compress with herbal components was associated with a statistically significant greater improvement in pain (P Ͻ .05). 17 The World Health Organization recommends hot compresses or a warm shower to help facilitate milk removal before feeding a newborn. 9 A systematic review of the literature found unpublished reports that cold compresses are recommended after or between feedings to decrease symptoms of pain and swelling.…”
Section: Hot and Cold Treatmentsmentioning
confidence: 95%
See 3 more Smart Citations
“…17 The hot compress with herbal components was associated with a statistically significant greater improvement in pain (P Ͻ .05). 17 The World Health Organization recommends hot compresses or a warm shower to help facilitate milk removal before feeding a newborn. 9 A systematic review of the literature found unpublished reports that cold compresses are recommended after or between feedings to decrease symptoms of pain and swelling.…”
Section: Hot and Cold Treatmentsmentioning
confidence: 95%
“…Results of the study revealed that both treatments reduced pain scores: hot compresses decreased pain scores from 5.8 to 2.8 (on a 10‐point scale; P < .001), and the hot, herbal compresses decreased reported pain scores from 6.9 to 1.0 ( P < .001) . The hot compress with herbal components was associated with a statistically significant greater improvement in pain ( P < .05) . The World Health Organization recommends hot compresses or a warm shower to help facilitate milk removal before feeding a newborn .…”
Section: Prevention and Treatment Of Primary Breast Engorgementmentioning
confidence: 98%
See 2 more Smart Citations
“…Breastfeeding has many advantages for both mothers and infants. Several factors related to the mother and the baby such as the technique used in breastfeeding, especially mother-infant positioning, latch, and suckling by the infant have been shown to be important for the effective transfer of milk from the breast to the child as well as for preventing nipple damage [2,3]. Breast milk contains nutrients at percentages exactly suited to the needs of the infant for growth and development [4].…”
Section: Background Of the Studymentioning
confidence: 99%